2023
DOI: 10.1038/s41598-023-29634-5
|View full text |Cite
|
Sign up to set email alerts
|

Low hemoglobin and PSA kinetics are prognostic factors of overall survival in metastatic castration-resistant prostate cancer patients

Abstract: The objective of this study was to identify the prognostic factors and to propose a new risk model in metastatic castration-resistant prostate cancer (mCRPC) patients. The clinical data were retrospectively obtained for 102 mCRPC patients who received cancer treatment between 2005 and 2018 at the University of Tokyo Hospital. We investigated clinical and pathological parameters, including prostate-specific antigen (PSA) kinetic profiles under androgen deprivation treatment, and identified predictors of overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…IL-6 has also been shown to act as an autocrine growth factor that inhibits apoptosis in prostate cancer [29]. Finally, the signi cant reduction in blood haemoglobin concentration (Hb) in PCa group compared with BPH group is consistent with recent report by Kaya et al and Tanno et al [23,30]. The plausible ascribed mechanism(s) by which the presence of a tumour might leads to low blood Hb could be as result of the induction of the ironregulatory hormone, hepcidin, by in ammatory cytokines, especially IL-6 [31].…”
Section: Discussionsupporting
confidence: 82%
“…IL-6 has also been shown to act as an autocrine growth factor that inhibits apoptosis in prostate cancer [29]. Finally, the signi cant reduction in blood haemoglobin concentration (Hb) in PCa group compared with BPH group is consistent with recent report by Kaya et al and Tanno et al [23,30]. The plausible ascribed mechanism(s) by which the presence of a tumour might leads to low blood Hb could be as result of the induction of the ironregulatory hormone, hepcidin, by in ammatory cytokines, especially IL-6 [31].…”
Section: Discussionsupporting
confidence: 82%
“…Anemia that typically manifests as low Hb is an indicator of tumor load and the overall physiological response of patients. Hemoglobin is acknowledged as a prognostic factor in CRPC, particularly for patients treated with docetaxel [ 25 27 ]. While changes in other biomarkers after completing the entire course of therapy did not significantly differ regardless of flare, anemia progressed in 42 of 46 patients without flare.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Taylor et al [ 18 ] demonstrated that preoperative anemia is linked to reduced overall survival in patients undergoing lung cancer surgery. Hakozaki et al [ 19 ] identified low HGB levels (< 11 g/dL) as a prognostic risk factor for PRCA patients. Regarding BLCA, individuals with higher HGB levels are less likely to develop the disease, with high HGB serving as a protective factor in patient prognosis [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, both earlier research and our retrospective analysis have indicated that fluctuations in HGB levels are associated with the risk of at least 10 malignant tumors. Notably, for PRCA, previous studies have reported the relationship between high HBG values and the favorable prognosis of this disease [ 19 , 22 , 23 ]. This is also verified in our analysis of the in-house data.…”
Section: Discussionmentioning
confidence: 99%